Voting with their Feet: Women’s Flight to Harare during Zimbabwe’s Liberation War - Chadya, Joyce (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2007)
AbstractThis paper explores the experiences of Zimbabwean rural women forced to relocate to the city of Harare during the liberation war in the 1970s. Women found themselves squeezed between a repressive colonial government and coercive guerrilla armies. The accompanying war-induced violence from both sides of the combattants led to massive displacements as women and their families fled from the war-torn areas to urban centres like Harare. Within women’s stories of flight are reflections of gender relations in a war fought largely in the rural areas where women were the majority of the dwellers, and a war in which most of the combattants were male. Gender relations thus informed, and were influenced by the war. Women’s narratives also reveal the socio-economic and emotional costs of the war hardly acknowledged in the nationalist discourse about the liberation war. At the centre of these accounts is a revelation of resistance, courage, fear, and above all agency by rural women under very difficult circumstances.